The Interweaving of Love and Truth: Bernard Lonergan, Intellectual Conversion, and the Synodal Process - Gerard Kevin Whelan (Religions)
This article explores the relatively theoretical question of what contribution academic theology is making to the synodal process and how this interaction might deepen in the years to come. It stresses the importance of what it calls foundational theological questions, employing the thought of the Jesuit philosopher and theologian Bernard Lonergan to define this term. It traces how a slow awareness of the importance of such questions, and an explicit attention to the question of theological method that is related to this, began emerging in the Second Vatican Council. It then suggests that such questions have come closer to the center of attention in the synodal process launched by Pope Francis. It proposes that the synodal process in the future will benefit by making further use of the thought of Lonergan. It leaves to a further study the question of how clarifying foundational and methodological questions in theology might have consequences for Catholic education in general.